Applied Regression Modelling to Recommend Green Business Development in Vietnam - Nga, Lu Phi; Huy, Nguyen Quoc; Tam, Phan Thanh (Bright Publisher, 2024)
The green businesses engaged in environmentally friendly business activities, minimizing negative impacted on the ecosystem and used resources effectively. Green businesses contributed to the country's sustainable development goals and brought practical benefits to the businesses themselves. Therefore, the article aimed to identify the key factors affecting green business development and proposed policy implications for green business development. Based on the study goal, the authors surveyed 400 managers of green enterprises in Vietnam and applied simulation modelling based on the quantitative research method. The findings explored five critical factors affecting green business development: (1) financial incentives, (2) corporate strategy and culture, (3) technological innovation, (4) mechanisms and policies, and (5) regulatory environment. The novelty of this study is that it increased the level of reputation and trust of customers, partners, and the community. Green businesses built a positive brand image to affirm their social responsibility and pioneering role in environmental protection. Green businesses could also attract and retain talent when employees feel proud and attached to the business's mission. A significant benefit of green businesses was their contribution to protecting the living environment for humans and animals. The article’s contributions helped to reduce greenhouse gas emissions, air, water, and soil pollution, reduce waste, and increase energy and resource efficiency. Green business development can also support nature conservation activities, habitat restoration, and biodiversity maintenance. The article's contributions proposed recommendations to management agencies in developing and implementing mechanisms and policies to support and promoted businesses to build in a green direction.